2022
DOI: 10.1371/journal.pone.0262483
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Rowlands Universal Dementia Assessment Scale (RUDAS) to detect major neurocognitive disorder among elderly people in Ethiopia, 2020

Abstract: Background The Rowland Universal Dementia Assessment Scale (RUDAS) is currently widely used for research and clinical purposes in many countries. However, its applicability and validity have not been evaluated in the Ethiopian context so far. Therefore, we designed this study to assess the reliability and validity of Rowland Universal Dementia Assessment Scale to detect major neurocognitive disorder among older people in Ethiopia. Methods An institution-based cross-sectional study was conducted among selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In another study, native English speakers outperformed non‐native English speakers on several neuropsychological tests, 10 suggesting that delivering tasks in a non‐native language might negatively impact test performance. Similar observations have been reported for many other populations with diverse linguistic abilities, leading to the development of different language‐specific versions of these neuropsychological tests 11–17 . In this context, a plain translation of such tests might not be enough, that is, the transcripted word in another language might have a slightly different conceptual meaning and can bias test results.…”
Section: Introductionsupporting
confidence: 72%
“…In another study, native English speakers outperformed non‐native English speakers on several neuropsychological tests, 10 suggesting that delivering tasks in a non‐native language might negatively impact test performance. Similar observations have been reported for many other populations with diverse linguistic abilities, leading to the development of different language‐specific versions of these neuropsychological tests 11–17 . In this context, a plain translation of such tests might not be enough, that is, the transcripted word in another language might have a slightly different conceptual meaning and can bias test results.…”
Section: Introductionsupporting
confidence: 72%
“…The study was part of a larger study, and a further description of the methods can be found in another publication by the same authors. 18…”
Section: Methodsmentioning
confidence: 99%
“…A full description of the diagnostic criteria can be referred to from the APA's manual or in other publications. 1,18 Geriatrics Depression Scale (GDS) short form, a 15-item self-report measure by Yesavage et al with Yes/No questions, was used to assess depression. 21,22 The tool has also been applied among the Ethiopian older adults and was reported to have good internal consistency.…”
Section: Gold Standard Assessmentmentioning
confidence: 99%
“…Higher score indicated superior performance, whereas lower scores indicated poorer cognitive ability or dementia risk. Though not yet validated in Ghana, the RUDAS is a culturally neutral tool that has been used worldwide in Asia, Europe, and Africa [ 11 ]. Hence, its usage within the Ghanaian context was acceptable.…”
Section: Study Variablesmentioning
confidence: 99%
“…Hence, its usage within the Ghanaian context was acceptable. The psychometric properties of RUDAS have remained moderate to strong over time and across many cultures [ 12 , 13 ]. For this study, calculated Cronbach’s alpha estimating RUDAS’ reliability was an acceptable value of 0.71, according to conventional cut-offs [ 14 ].…”
Section: Study Variablesmentioning
confidence: 99%